Sosialisasi Pemanfaatan Eco Enzyme untuk Mengurangi Sampah Organik di Dawis Anggrek Desa Blederan, Wonosobo, Jawa Tengah - Siti Latifah; Ahmad Atho’ Mukhotib; Nadzir Nadzir; Doni Agil Pamungkas; Hermawan Hermawan (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2023)
Indonesia has a serious waste problem and needs attention from all parties. Waste management can be carried out based on the 4R principle, namely reduce, reuse, recycle and replace. Garbage itself consists of organic and inorganic waste. Organic waste that is over capacity and not managed properly can cause hazards such as odors, affecting water quality, reducing soil quality, and producing methane gas as a contributor to greenhouse gases which can cause environmental damage. One of the efforts to reduce organic waste is through the manufacture of eco enzymes as a natural fertilizer for plants while reducing the greenhouse effect. Activities are carried out through socialization methods and training in making eco enzymes. The results of the activity show that there is an increase in public understanding about the benefits of eco enzyme for the environment as well as how to make eco enzyme by utilizing kitchen waste that is found every day..